The Effect of Perceived Ease of Use, Perceived Usefulness, and Perceived Security on E-Wallet Continuance Intention of Shopeepay Through E-Satisfaction - Bayu Bagas Hapsoro; Kismiatun Kismiatun (Management Analysis Journal, 2022)
The development of digitalization flows coupled with the emergence of the new normal era of Covid-19 globally, including in Indonesia, has resulted in an increase in the use of digital payment instruments such as ShopeePay. This study examines the effect of perceived ease of use, perceived usefulness, perceived security and e-satisfaction on e-wallet Continuance intention of ShopeePay in generation Z in Demak City. This study aims to examine and analyze the effect of the e-satisfaction variable in mediating the perceived ease of use, perceived usefulness, and perceived security on e-wallet Continuance intention. The data analysis technique used in this study is the Structural Equation Model – Partial Least Square (SEM-PLS) version 3.0 analysis. This analysis technique can determine the simultaneous linear relationship between research variables and latent variables. The results of this study indicate that perceived ease of use and perceived usefulness do not have a direct influence on e-wallet Continuance intention. Meanwhile perceived security has a positive and significant effect on e-wallet Continuance intention. E-satisfaction can mediate the relationship between variables perceived ease of use, perceived usefulness, and perceived security on e-wallet Continuance intention. And there is a direct influence between e-satisfaction on e-wallet Continuance intention.